FOSTERING STUDENTS VOCABULARY MASTERY THROUGH COMPUTER GAMES - Mita Nur Aflah (Jurnal Ilmiah Spectral, 2016)
This study was to find out the extent to which computer games is applicable and influenced classroom practices and students’ performance. The study recorded the implementation of computer games in order to find the improvement in the teaching learning process, including students’ improvement in vocabulary mastery. The data were gathered from classroom observations and interview. The analysis showed how computer games gave an improvement in teaching learning process. It provided opportunities to practice and use the language, as well as stimulating students’ interest to participate in the classroom activities. They made noticeable progress in their language learning while gaining confidence in vocabulary mastery. In short, this study showed that computer games promoted students active participation in the activities with more opportunities to practice and use the vocabularies which in turn increased their positive attitude for language learning